Scanning and vicarious learning from adverse events in health care (Information Research: An International Electronic Journal)
Studies have shown that serious adverse clinical events occur in approximately 3%-10% of acute care hospital admissions, and one third of these adverse events result in permanent disability or death. These findings have led to calls for national medical error reporting systems and for greater organizational learning by hospitals. But do hospitals and hospital personnel pay enough attention to such risk information that they might learn from each other's failures or adverse events? This paper gives an overview of the importance of scanning and vicarious learning from adverse events. In it I propose that health care organizations' attention and information focus, organizational affinity, and absorptive capacity may each influence scanning and vicarious learning outcomes. Implications for future research are discussed.